LIKE, SHARE, (IN) SECURITY IN THE AGE OF INFLUENCERS - Ungur-Brehoi, Carmen (International Journal of Legal and Social Order, 2025)
Influencers occupy a powerful yet highly contested position in contemporary digital society, facing complex ethical, economic, and social challenges. Their impact on the society is huge, only that their messages can amplify polarization, toxicity, and harmful social behaviors. A simple post or story can create chaos for the audience by spreading unrealistic lifestyle content, manipulating the viewers by misinformation and low-quality knowledge. The present study analyzes some of the constraints that the public nowadays needs to face when it comes to choosing and following the content of influencers. Whether it's about the tension between authenticity and commercial dependency based on brand partnerships and platform monetization, maintaining credibility for creators becomes really difficult. Critical thinking of the audience is the only capacity that can separate a sincere message from hidden advertising and personal opinion. Influencers frequently address large and diverse audiences, including minors and vulnerable groups, yet they often operate without formal ethical training or regulatory oversight. The promotion of unrealistic standards raises serious concerns regarding psychological well-being, public health, and consumer safety. Algorithmic pressure, labour precarity, political instrumentalization are other aspects that we have to take into consideration. The content creators' capacity to shape opinions makes them targets for coordinated political messaging, propaganda, and commercial-political hybrid campaigns. Many lack the institutional safeguards, editorial standards, or fact-checking structures required to manage such influence responsibly. Legal and regulatory uncertainty, particularly regarding taxation, advertising transparency, data protection, and consumer rights often lag behind the speed of platform innovation. In the next pages, through some relevant examples from Romanian media, we will observe the most recent cases of the influencers' challenges, that reflect upon fascinated and dependent audiences